Qualification of Ultra Vires Act by Board of Directors Company in Indonesian Law and Court - Andika Pribadi Waruwu (LOCUS MEDIA PUBLISHING, 2022)
Ultra vires actions are actions without authority / outside the authority in the representation contract given by a legal entity to a person. But in fact, cases and arrangements regarding Ultra Vires have not fully accommodated what parameters actually become a benchmark for an action referred to as ultra vires action. Is it only if one of the company's organs takes action outside of its authority that harms the company, but what if one of the company's organs takes action outside of its authority but does not harm the company. Court decisions that are also different in deciding cases about ultra vires actions are also an issue that continues to be disputed today. Therefore, this paper is intended to find out and analyze the regulation of Ultra Vires actions in Indonesian legislation, the size of the board of directors' actions can be qualified as ultra vires actions, as well as the opinion of the Court by the Supreme Court judges in the case of ultra vires lawsuits. This research includes normative legal research and is descriptive in nature, using primary, secondary and tertiary legal materials collected by the library research method. Furthermore, legal material data is analyzed using qualitative data analysis methods. The results of the study found that the application of the ultra vires doctrine in Indonesia is more likely to be associated with a criminal act committed by the board of directors or management, which is made beyond or outside the authority stipulated in the company's Articles of Association. This is what should be a special concern for lawmakers in terms of formulating things that can be a benchmark for actions referred to as ultra vires, so that legal certainty can be achieved.